Confirming a beneficial effect of the six-minute walk test on exercise confidence in patients with heart failure. (February 2020) - Toukhsati, SR; Mathews, S; Sheed, A; Freijah, I; Moncur, L; Cropper, P; Ha, FJ; Hare, DL
Background: Low confidence to exercise is a barrier to engaging in exercise in heart failure patients. Participating in low to moderate intensity exercise, such as the six-minute walk test, may increase exercise confidence. Aim: To compare the effects of a six-minute walk test with an educational control condition on exercise confidence in heart failure patients. Methods: This was a prospective, quasi-experimental design whereby consecutive adult patients attending an out-patient heart failure clinic completed the Exercise Confidence Scale prior to and following involvement in the six-minute walk test or an educational control condition. Results: Using a matched pairs, mixed model design ( n =60; 87% male; Mage =58.87±13.16), we identified a significantly greater improvement in Total exercise confidence ( F (1, 54)=4.63, p =0.036, partial η 2= 0.079) and Running confidence ( F (1, 57)=4.21, p =0. 045, partial η 2= 0.069) following the six-minute walk test compared to the educational control condition. These benefits were also observed after adjustment for age, gender, functional class and depression. Conclusion: Heart failure patients who completed a six-minute walk test reported greater improvement in exercise confidence than those who read an educational booklet for 10 min. The findings suggest that the six-minute walk test may be used as a clinical tool to improve exercise confidence. Future research should test these results under randomized conditions and examine whether improvements in exercise confidence translate to greater engagement in exercise behavior.